A escuta qualificada como dispositivo no cuidado em saúde mental na atenção básica - Marchesan, Rafaela Quintana (2018)
This project aimed to comprehend the perception of community healthcare agents towards the listening mechanism, in the work with mental health demands. Therefore, it was aimed to understand, by the professionals’ point of view, which resources and conditions are important to perform a qualified listening; to identify ease and/or difficulties found by professionals when using listening in situations that involve psychological suffering; to comprehend the mobilised feelings when the professional performs the listening involving psychological suffering and, finally, to identify if professionals recognize results/effects on healthcare users throughout the opening for listening. As for the methodology, the project followed a clinicalqualitative approach and data collection occurred through a semi-directed interview of openended questions. There were interviewed eight community healthcare agents of a Family Health Strategy from Santa Maria. Data analysis was performed through content analysis. Results pointed out to the performance of a qualified listening, indeed, by research participants, with the integration of recommendations and attributes proposed by the literature. Besides that, participants affirmed that had perceived effects on healthcare users after the performance of the listening, and pointed out pleasing case reports when listening was applied as an intervention. Moreover, it was presented a concern with the phenomenon of suffering medicalisation, in which listening and other interventions that are considered soft were indicated as strategies in face of such phenomenon. Furthermore, the relation of proximity perceived between healthcare users and community healthcare agents was approached with ambiguity by participants, and there were pointed out its potentials and fragilities on the interventions and listening of these professionals. Participants mentioned difficulties with the topic of grief, as because of the relation of proximity with healthcare users, as due to doubts regarding the ways of approaching the subject with those users. Moreover, the intervention, in face of situations that involved risk of suicide, psychotic symptoms and crisis attention seem to have raised discomfort, fear and insecurity in the professionals who were interviewed. Nevertheless, it stands out that community healthcare agents have been using the resource of listening as a possibility of healthcare in face of such situations. Finally, the topic of social isolation and loneliness experienced by healthcare users was pointed out as an issue which professionals tend to consider hard to intervene and to listen to, although they aim to use some strategies to confront such phenomenon. Lastly, it is emphasized the necessity of community healthcare agents to possess tools and mechanisms to strengthen them in order to perform a qualified listening, such as the example of matrix support, of teamwork, of continuing education and of a well structured mental health network.